Impact of interventions and tumor stage on health-related quality of life in patients with hepatocellular carcinoma - Wehling, Cyrill; Hornuß, Daniel; Springfeld, Christoph; Hoffmann, Katrin; Chang, De-Hua; Naumann, Patrick; Mieth, Markus; Longerich, Thomas; Kratochwil, Clemens; Mehrabi, Arianeb; Gauss, Annika; Weiss, Karl Heinz; et al. (Journal of cancer research and clinical oncology, 2019)
Purpose: This study aims to examine the health-related quality of life in patients with hepatocellular carcinoma. Methods: 181 patients attending a tertiary center outpatient clinic were interviewed and completed the short form 36 (SF36) questionnaire. The SF36 was used to assess health-related QoL. Cross-sectional analyses by group (age, gender, clinical scores, systemic, and local interventions) as well sequel questionnaires were conducted. Results: Participants included were 79% (143/181) men [mean age at first SF36: 63.8 (± 12.3; 18.4-85.8) years]. Barcelona Clinic Liver Cancer (BCLC) stadium C was associated with significantly lower SF36 total scores, and elevated initial alpha-fetoprotein (AFP) concentrations were associated with lower SF36 functional and mental health sum scores throughout the course of the third questionnaire. Patients treated with sorafenib had within the sub-dimension scores a significantly lower result for role limitations due to physical health compared to patients without sorafenib treatment. Patients who underwent a transarterial chemoembolization (TACE) had within the sub-dimension scores a significantly higher result for control of pain compared to patients without TACE. Kaplan-Meier analysis revealed significant survival benefits for patients who underwent any intervention at the first SF36 (mean survival in years 4.3 vs. 1.6; P < 0.01) as well as for patients who underwent hepatic resection (mean survival in years 6.3 vs. 2.7; P < 0.0001). Conclusion: Advanced tumor stages marked by BCLC stadium C and elevated initial AFP concentrations were associated with lower SF36 total scores and functional sum scores, respectively. During the course of sorafenib treatment, the sub-dimensional score for role limitations due to physical health decreased significantly, whereas TACE performance was associated with a significant improvement of the control of body pain.